Endothelial glycocalyx injury is involved in heatstroke-associated coagulopathy and protected by N-acetylcysteine - Peng, Na; Geng, Yan; Ouyang, Jiafu; Liu, Shuai; Yuan, Fangfang; Wan, Yantong; Chen, Wenda; Yu, Baojun; Tang, Youqing; Su, Lei; Liang, Huaping; Wang, Jiang Huai; et al. (Frontiers in Immunology, 2023)
Introduction Damage to endothelial glycocalyx (EGCX) can lead to coagulation disorders in sepsis. Heat stroke (HS) resembles sepsis in many aspects; however, it is unclear whether EGCX injury is involved in its pathophysiology. The purpose of this study was to examine the relationship between the damage of EGCX and the development of coagulation disorders during HS. Methods We retrospectively collected 159 HS patients and analyzed coagulation characteristics and prognosis of HS patients with or without disseminated intravascular coagulation (DIC). We also replicated a rat HS model and measured coagulation indexes, pulmonary capillary EGCX injury in HS rats. Finally, we evaluated the effect of the antioxidant N-acetylcysteine (NAC) on HS-initiated EGCX injury and coagulation disorders. Results Clinical data showed that HS patients complicated with DIC had a higher risk of death than HS patients without DIC. In a rat HS model, we found that rats subjected to heat stress developed hypercoagulability and platelet activation at the core body temperature of 43°C, just before the onset of HS. At 24 h of HS, the rats showed a consumptive hypo-coagulation state. The pulmonary capillary EGCX started to shed at 0 h of HS and became more severe at 24 h of HS. Importantly, pretreatment with NAC substantially alleviated EGCX damage and reversed the hypo-coagulation state in HS rats. Mechanically, HS initiated reactive oxidative species (ROS) generation, while ROS could directly cause EGCX damage. Critically, NAC protected against EGCX injury by attenuating ROS production in heat-stressed or hydrogen peroxide (H2O2)-stimulated endothelial cells. Discussion Our results indicate that the poor prognosis of HS patients correlates with severe coagulation disorders, coagulation abnormalities in HS rats are associated with the damage of EGCX, and NAC improves HS-induced coagulopathy, probably through its protection against EGCX injury by preventing ROS generation.